2017
DOI: 10.1111/ejed.12211
|View full text |Cite
|
Sign up to set email alerts
|

Beyond educational attainment: The importance of skills and lifelong learning for social outcomes. Evidence for Europe from PIAAC

Abstract: Empirical evidence suggests that educational attainment nurtures people's social outcomes and promotes active participation in society and stability. However, it is unclear to what extent other types of human capital also correlate with social outcomes. Hence, we explored the opportunity offered by the PIAAC survey through its provision of information on educational attainment, observed individual key skills proficiency, and participation in adult education and training (adult lifelong learning). We therefore … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 26 publications
(22 reference statements)
1
25
0
Order By: Relevance
“… Reference group: Literacy levels below 1 and 1. The data were culled from Costa et al () and Vera‐Toscano et al (). …”
Section: The Benefits and Challenges Of Increasing Literacy Skillsmentioning
confidence: 99%
“… Reference group: Literacy levels below 1 and 1. The data were culled from Costa et al () and Vera‐Toscano et al (). …”
Section: The Benefits and Challenges Of Increasing Literacy Skillsmentioning
confidence: 99%
“…However, earlier studies using less restrictive models found much stronger associations (e.g. 70% in Vera-Toscano et al, 2017). Hence, our contribution is that we Does participation in adult education increase volunteering?…”
Section: Discussionmentioning
confidence: 67%
“…Regarding content, existing research suggests that AE representing distinct pedagogies and promoting public enlightenment can be effective in changing people's values, attitudes and dispositions and hence their preferences (De Greef, Verté, & Segers, 2015;Desjardins, 2017;Paterson, 2009;Vera-Toscano et al, 2017). Analysing British longitudinal data, Paterson (2009), for instance, found a positive effect of AE courses in the social sciences and humanities on socially liberal values and civic participation.…”
Section: How Adult Education Affects Determinants Of Change In Voluntmentioning
confidence: 99%
See 1 more Smart Citation
“…Some evidence using PIAAC data reported in OECD (2017b) shows that cognitive skills are positively related to political participation, even after controlling for education. Vera-Toscano et al (2017) analyse the links between education, skills, and participation in adult learning and two social outcomes from PIAAC: interpersonal trust and volunteering. They show that cognitive skills matter for social outcomes, over and above the impact of formal education.…”
Section: Well-beingmentioning
confidence: 99%